Intraplaque neovascularization attenuated statin benefit on atherosclerotic plaque in CAD patients: A follow-up study with combined imaging modalities. (August 2019) - Liu, Xinxin; Sun, Changbin; Gu, Xia; Liu, Xianglan; Wang, Xuedong; Wang, Xueyu; Xie, Zulong; Tian, Jinwei; Yu, Bo
Abstract: Background and aims: Plaque progression increases the risk of a cardiovascular event. This study aims to determine whether intraplaque neovascularization (NV) associates with a greater risk of plaque progression. Methods: Baseline and 12-month follow-up IVUS was used in combination with baseline OCT to assess 164 non-culprit plaques in 118 CAD patients. A generalized estimating equation approach with exchangeable correlation structure was used to correct for the dependency of repeated measurements. Results: Patients were divided into two groups according to NV (52 patients with 62 NV plaques, 66 patients with 102 non-NV plaques). Non-culprit plaques in the NV group exhibited a more frequent occurrence of TCFA ( p = 0.004), macrophage ( p = 0.005), cholesterol crystal ( p = 0.012), calcification ( p = 0.030), thinner fibrous cap thickness (FCT) [(86.8 ± 55.1) vs . (127.4 ± 70.1) μm, p = 0.015], larger lipid arc [(219.5 ± 66.9) vs . (179.8 ± 61.4), p = 0.002] compared to the non-NV group. A large change in percent atheroma volume (PAV), plaque plus media cross-sectional area (P&M CSA), plaque volume, and plaque burden was observed from baseline to follow-up in the NV group. Changes in P&M CSA, plaque volume, and plaque burden showed significant differences in fibroatheroma with NV. Intraplaque NV could predict a high risk of plaque progression despite statin therapy [OR 6.521 (95% CI 2.457–17.308), p < 0.001]. Conclusions: NV might attenuate the benefits of statin therapy in plaque progression. This study may provide a new basis for anti-angiogenic strategies to prevent atherosclerotic plaque progression. Graphical abstract: Image 1 Highlights: Plaques with neovascularization exhibited more vulnerable characteristics. Neovascularization attenuated the benefit of statins on plaque progression. Neovascularization had a stronger influence on fibroatheroma than fibrous plaque.